Serum p-Cresyl Sulfate Is Independently Associated with Aortic Stiffness in Non-Dialysis Chronic Kidney Disease Patients - Yahn-Bor Chern; Ken Lee Chia; Chin-Hung Liu; Yu-Li Lin; Jen-Pi Tsai; Bang-Gee Hsu (Life, 2025)
p-Cresyl sulfate (PCS), a gut-derived uremic toxin with proinflammatory and cytotoxic effects, has been implicated in cardiovascular injuries among patients with chronic kidney disease (CKD). Aortic stiffness (AS), assessed by carotid–femoral pulse wave velocity (cfPWV), is a recognized predictor of cardiovascular risk. This study investigated the association between serum PCS levels and AS in patients with nondialysis-dependent CKD. In total, 165 patients with nondialysis-dependent CKD were enrolled. Clinical data and fasting blood samples were collected. Arterial stiffness (AS) was assessed bilaterally by measuring carotid–femoral pulse wave velocity (cfPWV) on both the left and right sides. A value above 10 m/s was considered indicative of increased stiffness. Serum PCS levels were quantified using high-performance liquid chromatography–mass spectrometry. Fifty patients (30.3%) had AS. The AS group was significantly older and had higher diabetes prevalence, systolic blood pressure, fasting glucose, urinary protein-creatinine ratio, and PCS levels than the control group. In the multivariate analysis, both PCS (odds ratio [OR]: 1.097; 95% confidence interval [CI]: 1.024–1.175; p = 0.008) and age (OR: 1.057; 95% CI: 1.025–1.090; p < 0.001) were independently associated with AS. In conclusion, elevated serum PCS and older age were independently associated with AS. Thus, PCS is a potential early marker of vascular damage in CKD.